Locked-in syndrome following a king cobra (Ophiophagus hannah) envenomation - Ahmad Khaldun Ismail,; Mohd Fyzal B,; Soo, CI; Yeap, BT; Mohamed Faisal AH, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
The incidence of envenoming from king cobra, Ophiophagus hannah in human is relatively rare. Its venom acts on the postsynaptic region of the neuromuscular junction causing descending flaccid paralysis. Locked-in syndrome is a clinical state of inability to provide motor response in a conscious patient. Many reported cases of locked-in syndrome following neurotoxic snake-bite mimics brain death. We report a case of a middle aged man who presented with progressive neurological deficit following a king cobra bite over his right arm. He had local and systemic neurotoxic envenoming. His condition deteriorated, and was intubated and ventilated in the emergency department. He received a total of 33 vials of the Ophiophagus hannah monospecific antivenom and subsequently recovered well with no neurological deficit. Retrospectively, he was able to recall the events and while he was lying paralysed and intubated under minimal sedation in the intensive care unit. He described it as a terrifying and painful experience. This case highlights the rare presentation of locked-in syndrome following a systemic envenoming from a king cobra bite. It is important to differentiate neurotoxic snake envenoming lock-in syndrome from brain dead. Patients are unable to respond to physical pain and require adequate analgesia. A patient suffering this highly distressing experience may require psychological support.